Answer:
A. The lowercase symbol, p, represents the probability of getting a test statistic at least as extreme as the one representing sample data and is needed to test the claim.
Step-by-step explanation:
The conditions required for testing of a claim about a population proportion using a formal method of hypothesis testing are:
1) The sample observations are a simple random sample.
2) The conditions for a binomial distribution are satisfied
3) The conditions np5 and nq5 are both satisfied. i.e n: p≥ 5and q≥ 5
These conditions are given in th options b,c and d.
Option A is not a condition for testing of a claim about a population proportion using a formal method of hypothesis testing.
That's easy it is 5,300,000 I think by the way Might be wrong I hurt my eye so yea don't say I am not good at math it is my eye hurting or it can be 5,300,288
Answer: Its b also y u test so ez what grade u in lol?
Answer:β=√10 or 3.16 (rounded to 2 decimal places)
Step-by-step explanation:
To find the value of β :
- we will differentiate the y(x) equation twice to get a second order differential equation.
- We compare our second order differential equation with the Second order differential equation specified in the problem to get the value of β
y(x)=c1cosβx+c2sinβx
we use the derivative of a sum rule to differentiate since we have an addition sign in our equation.
Also when differentiating Cosβx and Sinβx we should note that this involves function of a function. so we will differentiate βx in each case and multiply with the differential of c1cosx and c2sinx respectively.
lastly the differential of sinx= cosx and for cosx = -sinx.
Knowing all these we can proceed to solving the problem.
y=c1cosβx+c2sinβx
y'= β×c1×-sinβx+β×c2×cosβx
y'=-c1βsinβx+c2βcosβx
y''=β×-c1β×cosβx + (β×c2β×-sinβx)
y''= -c1β²cosβx -c2β²sinβx
factorize -β²
y''= -β²(c1cosβx +c2sinβx)
y(x)=c1cosβx+c2sinβx
therefore y'' = -β²y
y''+β²y=0
now we compare this with the second order D.E provided in the question
y''+10y=0
this means that β²y=10y
β²=10
B=√10 or 3.16(2 d.p)
Hey there!
You can use distributive property, as I mentioned in your previous questions.
multiply...
2a² × a = 2a³
2a² × -1 = -2a²
a × a = a²
a × -1 = -a
3 × a = 3a
3 × -1 = -3
add all those terms..
2a³ - 2a² + a² - a + 3a - 3
add the like terms
2a³ - a² + 2a - 3
Hope this helped :)